2001
DOI: 10.3402/fnr.v45i0.1792
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable and fruit consumption and its determinants in young Finnish adults

Abstract: Background:The low consumption of vegetables and fruit among young adults is a growing universal concern. Objective: To examine determinants of vegetable consumption among young Finnish adults aged 25 to 34 years. Design: A questionnaire covering health behaviour, socio-economic status and food frequencies was sent to subjects in 1997 (participation rate 64%, n=1589). A 24-h recall was collected for a subsample of these participants. Results: Education, parental status, place of midday meal, perception of diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 16 publications
5
17
0
Order By: Relevance
“…In line with previous studies in Europe and the Nordic countries (Osler, 1993;Roos et al, 1996;Lynch et al, 1997;Hjartaker and Lund, 1998;Irala-Estevez et al, 2000;Lallukka et al, 2001;Roos et al, 2001;Perrin et al, 2002;Agudo et al, 2002a;Dynesen et al, 2003), we found clear differences in daily vegetable consumption by educational level and household income during all periods studied. We found that socioeconomic differences in daily consumption of vegetables decreased between the years 1979 and 2002 and this decrease mainly occurred after 1998.…”
Section: Trends Of Socioeconomic Differencessupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous studies in Europe and the Nordic countries (Osler, 1993;Roos et al, 1996;Lynch et al, 1997;Hjartaker and Lund, 1998;Irala-Estevez et al, 2000;Lallukka et al, 2001;Roos et al, 2001;Perrin et al, 2002;Agudo et al, 2002a;Dynesen et al, 2003), we found clear differences in daily vegetable consumption by educational level and household income during all periods studied. We found that socioeconomic differences in daily consumption of vegetables decreased between the years 1979 and 2002 and this decrease mainly occurred after 1998.…”
Section: Trends Of Socioeconomic Differencessupporting
confidence: 93%
“…Previous studies on socioeconomic differences in vegetable consumption have used different dietary assessment methods, such as food records (Roos et al, 1996;Lynch et al, 1997;Groth et al, 2001;Hulshof et al, 2003), 24 h recalls (Popkin et al, 1996;Lallukka et al, 2001;Giskes et al, 2002;Agudo et al, 2002a) and food frequency questionnaires including varying number of items (Prattala et al, 1992;Smith and Baghurst, 1992;Osler, 1993;Shimakawa et al, 1994;Hjartaker and Lund, 1998;Fraser et al, 2000;Mishra et al, 2002;Perrin et al, 2002;Dynesen et al, 2003). Our data included answers to one frequency question on consumption of fresh vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…The lunch served in staff canteens always includes a free salad of fresh vegetables, so it seems reasonable that lunch at a staff canteen promotes the consumption of vegetables. Other studies also support the finding that having lunch at staff canteens promotes the consumption of vegetables 16,17 . However, we do not know if the participants ate their cooked vegetables as fried and whether fat was added or not.…”
Section: Discussionmentioning
confidence: 69%
“…(8) How mentally demanding is your job? (9) Is there dust at your workplace? (10) Do you use solvents in your job, and do they bother you?…”
Section: Appendix -Variables Used In Factor Analysismentioning
confidence: 99%
“…Employees' food choices at workplace cafeterias are indeed found to be more in line with nutritional recommendations than at other eating places, since, for instance, fresh vegetables, vegetarian foods and fish are favoured [9][10][11] .…”
mentioning
confidence: 99%